Preparation method and application of MnV13 cluster aqueous zinc ion battery positive electrode material based on tetrabutylammonium coating
By coating the MnV13 cluster with tetrabutylammonium, the phase stability and ion transport problems of the polymetal oxygen cluster positive electrode material are solved, and the electrochemical energy storage performance and cyclic stability of aqueous zinc ion batteries are significantly improved.
Patent Information
- Application Number
- CN202510085238.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing polymetal oxygen clusters, as the positive electrode material of aqueous zinc ion batteries, have limited phase stability, limited ion transport, excess crystallization water, and low pseudocapacitance contribution rate, resulting in low discharge capacity and durability.
Tetrabutylammonium is used to coat the MnV13 cluster, and TBA cation is coated with MnV13 cluster through ion exchange reaction to form a stable structure, and the residual moisture is removed through calcination to improve the electrochemical activity and stability of the material.
It significantly improves the electrochemical energy storage performance and cycle stability of the material, enhances the kinetics of the electrochemical reaction and ion transport performance, and extends the cycle life of the battery.
Smart Images

Figure CN119905559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aqueous zinc ion batteries. Background Art
[0002] With the continuous growth of global energy demand and the gradual depletion of fossil energy, the demand for a low-carbon economy has become increasingly urgent, which has promoted profound changes in the energy consumption structure and spawned a trend of transformation from traditional fossil fuels to renewable energy and sustainable alternative energy. As a key tool to support sustainable and intermittent energy utilization, electrochemical energy storage systems have become an important technology for fast and efficient energy storage and release. Among them, lithium-ion batteries (LIBs) have shown good adaptability and reliability in many fields such as portable devices and electric vehicles due to their high energy density, long cycle life, low self-discharge rate and fast charging capability. However, LIBs face some limitations in grid-scale energy storage, such as the high cost caused by the scarcity of lithium resources, the potential harm to the environment and safety hazards of flammable organic electrolytes. Compared with the above battery systems, aqueous zinc-ion batteries show great potential in the future large-scale energy storage field due to their advantages of high safety, environmental friendliness, abundant zinc reserves, low cost and high energy density.
[0003] Polyoxometallic clusters have been widely regarded as promising candidates for cathode materials of aqueous zinc-ion batteries in recent years due to their rich redox properties, precise molecular-level structures, and excellent electronic controllability. Among them, vanadium-based polyoxometallic clusters have attracted much attention due to their multi-electron reaction mechanisms and complex and rich redox kinetic behaviors. However, their direct application in aqueous electrolytes is affected by many limiting factors, such as insufficient phase stability, limited ion transport, and the presence of excess crystalline water, which significantly restrict the theoretical capacity realization and cycle stability of the materials. Summary of the invention
[0004] The present invention aims to solve the problems of limited phase stability, limited ion transport, excess crystal water and low pseudocapacitance contribution rate of existing polymetallic oxygen clusters as positive electrode materials for aqueous zinc ion batteries, resulting in low discharge capacity and durability, and further provide a MnV based on tetrabutylammonium coating 13 Preparation method and application of positive electrode material for cluster aqueous zinc ion battery.
[0005] A MnV based on tetrabutylammonium coating 13 The method for preparing the positive electrode material of the cluster water system zinc ion battery is carried out according to the following steps:
[0006] 1. MnV 13 Dissolve in deionized water to obtain MnV 13 Solution;
[0007] 2. dissolving tetrabutylammonium chloride in deionized water to obtain a tetrabutylammonium chloride solution;
[0008] 3. Under stirring conditions, MnV 13 The solution is slowly added to the tetrabutylammonium chloride solution and stirred, and then the mixed solution is concentrated, centrifuged, washed and dried to obtain a dry powder;
[0009] 4. The dried powder was calcined under argon atmosphere to obtain tetrabutylammonium-coated MnV 13 , that is, to complete the MnV based on tetrabutylammonium coating 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery;
[0010] The tetrabutylammonium-coated MnV 13 The chemical formula is (NH4)2(C 16 H 36 N)5MnV 13 O 38 .
[0011] Application: It is used to prepare the positive electrode of aqueous zinc-ion batteries.
[0012] The beneficial effects of the present invention are:
[0013] 1. The present invention discloses a method of coating MnV with tetrabutylammonium 13 A method for preparing a high-performance pseudocapacitor positive electrode material, the method firstly mixes TBA cations and MnV 13 The anion solution was then used to simply coat MnV with TBA cations using an ion exchange reaction in aqueous solution. 13 Cluster (TBA-MnV 13 ). The positively charged cation part is connected with MnV 13 The negatively charged anions on the clusters are electrostatically attracted to form a stable structure, and then calcination is performed to ensure that the residual water is completely removed. The removal of crystal water can improve the activity of polymetallic oxygen clusters. At the same time, due to the MnV 13 The innovative compound with TBA introduces structural disorder and reduces crystallinity, all of which synergistically enhance the electrochemical activity and stability of the material and improve the electrochemical energy storage performance of the material. The above preparation method is simple in process, easy to operate and repeat, universal, can be used for large-scale production, and has good application prospects.
[0014] 2. The present invention also discloses the above-mentioned tetrabutylammonium-coated MnV 13 The application of high-performance pseudocapacitive materials in aqueous zinc-ion battery positive electrodes. When used as positive electrode materials for aqueous zinc-ion batteries, this material can promote Zn by enhancing the contribution of surface pseudocapacitance. 2+The rapid storage of ions ensures fast electrochemical reaction kinetics (the variable scan rate CV calculation results show that with the increase of scan rate, the capacitance contribution gradually increases and is greater than that of MnV under the same conditions). 13 In addition, due to the coating effect of TBA in the material, when the material is used as the positive electrode material of aqueous zinc-ion batteries, the cycle stability of the battery system is significantly improved (at a current density of 1A / g, after 2700 cycles, TBA-MnV 13 The specific capacity of the positive electrode is still as high as 258.7 mAh g -1 ; Compared with MnV 13 After 2700 cycles, the specific capacity is only 19.7 mAh g -1 ). In summary, MnV coated with tetrabutylammonium 13 The kinetic and electrochemical performances of high-performance pseudocapacitive materials in aqueous zinc-ion batteries have been significantly improved.
[0015] Instruction Manual
[0016] Figure 1 The TBA-MnV prepared in Example 1 13 With MnV 13 X-ray diffraction image comparison chart;
[0017] Figure 2 The TBA-MnV prepared in Example 1 13 , TBA and MnV 13 Infrared spectrum of
[0018] Figure 3 The TBA-MnV prepared in Example 1 13 Transmission electron microscope image of
[0019] Figure 4 The TBA-MnV prepared in Example 1 13 High-resolution transmission electron microscopy images of
[0020] Figure 5 The TBA-MnV prepared in Example 1 13 Elemental distribution map of energy dispersive X-ray spectroscopy;
[0021] Figure 6 The TBA-MnV prepared in Example 1 13 Thermogravimetric analysis curves under oxygen atmosphere;
[0022] Figure 7 For Example 3, TBA-MnV 13 and MnV 13The prepared aqueous zinc ion battery positive electrode assembled button cell was tested at a voltage of 0.2 V to 1.8 V and a scan rate of 0.5 mV s -1 Cyclic voltammetry curves under
[0023] Figure 8 For Example 3, TBA-MnV 13 and MnV 13 The charge and discharge curves of the button cell assembled with the prepared aqueous zinc ion battery positive electrode;
[0024] Fig. 9 For Example 3, TBA-MnV 13 and MnV 13 The button cell assembled with the prepared aqueous zinc ion battery positive electrode was operated at a current density of 0.2A -1 ~9Ag -1 The rate performance test curve below;
[0025] Fig.10 For Example 3, TBA-MnV 13 and MnV 13 Electrochemical impedance spectroscopy test of button cells assembled with the prepared aqueous zinc ion battery positive electrode;
[0026] Fig.11 For Example 3, TBA-MnV 13 The CV curves of the button cells assembled with the prepared aqueous zinc-ion battery cathode were measured at different scan rates;
[0027] Fig.12 for Fig.11 b values of the four groups of redox peaks;
[0028] Fig.13 For Example 3, TBA-MnV 13 The diffusion / capacitance contribution ratio calculated after measuring the CV curves of the prepared aqueous zinc-ion battery cathode assembled button cells at different scan rates;
[0029] Fig.14 For Example 3, MnV 13 The CV curves of the button cells assembled with the prepared aqueous zinc-ion battery cathode were measured at different scan rates;
[0030] Fig.15 for Fig.14 b values of the four groups of redox peaks;
[0031] Fig.16 For Example 3, MnV 13 The diffusion / capacitance contribution ratio of the button cell assembled with the prepared aqueous zinc-ion battery cathode was calculated after measuring the CV curve at different scan rates;
[0032] Fig.17 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the initial stage TBA-MnV 13 V 2p X-ray photoelectron spectrum;
[0033] Fig.18 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the discharge stage TBA-MnV 13 V 2p X-ray photoelectron spectrum;
[0034] Fig.19 For Example 3, TBA-MnV 13 The button cell assembled with the prepared aqueous zinc ion battery cathode during the charging stage TBA-MnV 13 V 2p X-ray photoelectron spectrum;
[0035] Fig. 20 For Example 3, MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the initial stage MnV 13 V 2p X-ray photoelectron spectrum;
[0036] Fig.21 For the use of MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the discharge stage MnV 13 V 2p X-ray photoelectron spectrum;
[0037] Fig. 22 For the use of MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the charging stage MnV 13 V 2p X-ray photoelectron spectrum;
[0038] Fig.23 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell during the second charge and discharge (activation) period 51 V NMR spectrum;
[0039] Fig.24 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the twelfth cycle (after activation) 51 V NMR spectrum;
[0040] Fig.25For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the discharge stage TBA-MnV 13 Zn 2p X-ray photoelectron spectrum of the positive electrode;
[0041] Fig.26 For Example 3, TBA-MnV 13 The button cell assembled with the prepared aqueous zinc ion battery cathode during the charging stage TBA-MnV 13 Zn 2p X-ray photoelectron spectrum of the positive electrode;
[0042] Fig. 27 For Example 3, MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell at 1.0Ag -1 Cyclic performance diagram of 2700 cycles at a current density of , 1 is the Coulomb efficiency curve, 2 is the discharge specific capacity curve;
[0043] Fig.28 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell at 1.0Ag -1 Cyclic performance diagram of 2700 cycles at a current density of , 1 is the Coulomb efficiency curve, 2 is the discharge specific capacity curve;
[0044] Fig.29 For Example 3, TBA-MnV 13 and MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell at 0.2Ag -1 300 cycles test diagram at current density;
[0045] Fig.30 For Example 3, TBA-MnV 13 The energy density and power density of the button cell assembled with the prepared aqueous zinc-ion battery cathode are compared with those of the reported vanadium-based cathode materials;
[0046] Fig.31 For Example 3, TBA-MnV 13 The self-discharge test of the button cell assembled with the prepared aqueous zinc ion battery positive electrode after standing for 48 hours;
[0047] Fig.32 For Example 3, MnV 13 Self-discharge test diagram of the button battery assembled with the prepared aqueous zinc-ion battery positive electrode after standing for 48 hours. DETAILED DESCRIPTION
[0048] Specific embodiment 1: This embodiment is a MnV based on tetrabutylammonium coating 13 The method for preparing the positive electrode material of the cluster water system zinc ion battery is carried out according to the following steps:
[0049] 1. MnV 13 Dissolve in deionized water to obtain MnV 13 Solution;
[0050] 2. dissolving tetrabutylammonium chloride in deionized water to obtain a tetrabutylammonium chloride solution;
[0051] 3. Under stirring conditions, MnV 13 The solution is slowly added to the tetrabutylammonium chloride solution and stirred, and then the mixed solution is concentrated, centrifuged, washed and dried to obtain a dry powder;
[0052] 4. The dried powder was calcined under argon atmosphere to obtain tetrabutylammonium-coated MnV 13 , that is, to complete the MnV based on tetrabutylammonium coating 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery;
[0053] The tetrabutylammonium-coated MnV 13 The chemical formula is (NH4)2(C 16 H 36 N)5MnV 13 O 38 .
[0054] This specific embodiment is a tetrabutylammonium coated MnV 13 (TBA-MnV 13 ) cathode, this coating strategy aims to utilize MnV 13 The structure and electronic properties of the Zn2+ electrode are improved by coating to improve its stability and ion diffusion pathway. Compared with the traditional embedded electrode, it significantly improves the performance of aqueous zinc-ion batteries through an efficient pseudocapacitive mechanism, achieving fast and stable Zn2+ 2+ The insertion does not affect the integrity of the electrode structure. The positive electrode material is low in cost, safe and environmentally friendly, and easy to prepare on a large scale.
[0055] The beneficial effects of this embodiment are:
[0056] 1. This embodiment discloses a method of coating MnV with tetrabutylammonium 13 A method for preparing a high-performance pseudocapacitor positive electrode material, the method firstly mixes TBA cations and MnV 13 The anion solution was then used to simply coat MnV with TBA cations using an ion exchange reaction in aqueous solution. 13 Cluster (TBA-MnV 13). The positively charged cation part is connected with MnV 13 The negatively charged anions on the clusters are electrostatically attracted to form a stable structure, and then calcination is performed to ensure that the residual water is completely removed. The removal of crystal water can improve the activity of polymetallic oxygen clusters. At the same time, due to the MnV 13 The innovative compound with TBA introduces structural disorder and reduces crystallinity, all of which synergistically enhance the electrochemical activity and stability of the material and improve the electrochemical energy storage performance of the material. The above preparation method is simple in process, easy to operate and repeat, universal, can be used for large-scale production, and has good application prospects.
[0057] 2. This embodiment also discloses the above tetrabutylammonium-coated MnV 13 The application of high-performance pseudocapacitive materials in aqueous zinc-ion battery positive electrodes. When used as positive electrode materials for aqueous zinc-ion batteries, this material can promote Zn by enhancing the contribution of surface pseudocapacitance. 2+ The rapid storage of ions ensures fast electrochemical reaction kinetics (the variable scan rate CV calculation results show that with the increase of scan rate, the capacitance contribution gradually increases and is greater than that of MnV under the same conditions). 13 In addition, due to the coating effect of TBA in the material, when the material is used as the positive electrode material of aqueous zinc-ion batteries, the cycle stability of the battery system is significantly improved (at a current density of 1A / g, after 2700 cycles, TBA-MnV 13 The specific capacity of the positive electrode is still as high as 258.7 mAh g -1 ; Compared with MnV 13 After 2700 cycles, the specific capacity is only 19.7 mAh g -1 ). In summary, MnV coated with tetrabutylammonium 13 The kinetic and electrochemical performances of high-performance pseudocapacitive materials in aqueous zinc-ion batteries have been significantly improved.
[0058] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: the MnV 13 The mass ratio of the ionizer to the volume of deionized water is 1 g: (20-30) mL. The rest is the same as the first embodiment.
[0059] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass ratio of tetrabutylammonium chloride to deionized water in step 2 is 1 g: (50-60) mL. Other aspects are the same as specific implementation method 1 or 2.
[0060] Specific implementation method 4: This implementation method is different from one of the specific implementation methods 1 to 3 in that: the MnV 13The volume ratio of the solution to the tetrabutylammonium chloride solution is 1:(3-4). Other aspects are the same as those of the first to third embodiments.
[0061] Specific embodiment 5: This embodiment differs from the specific embodiments 1 to 4 in that: in step 3, at a rotation speed of 500 rpm to 800 rpm, MnV is added at a rate of 1 mL / min to 2 mL / min. 13 The solution is slowly added into the tetrabutylammonium chloride solution and stirred for 1 to 2 hours. The rest is the same as the specific embodiments 1 to 4.
[0062] Specific implementation method 6: This implementation method is different from the specific implementation methods 1 to 5 in that: the concentrated mixed solution described in step 3 is specifically concentrated by using a rotary evaporator at a temperature of 50°C to 60°C and a rotation speed of 100rpm to 120rpm until the solvent is completely evaporated; the centrifugal washing described in step 3 is specifically using deionized water, at a rotation speed of 8000rpm to 10000rpm, centrifugal washing for 5min to 10min, and the centrifugal washing is repeated ≥ 3 times. The rest is the same as the specific implementation methods 1 to 5.
[0063] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that the drying described in step 3 is specifically performed at a temperature of 50° C. to 60° C. and vacuum drying for 12 h to 16 h. The rest is the same as Specific embodiments 1 to 6.
[0064] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: in step 4, the temperature is raised to 200°C to 250°C at a heating rate of 3°C / min to 5°C / min under an argon atmosphere, and then calcined for 5h to 6h under the conditions of an argon atmosphere and a temperature of 200°C to 250°C. The rest is the same as specific embodiments 1 to 7.
[0065] Specific embodiment 9: This embodiment is based on a tetrabutylammonium-coated MnV 13 The application of cluster aqueous zinc ion battery positive electrode material is used to prepare aqueous zinc ion battery positive electrode.
[0066] Specific embodiment 10: This embodiment is different from specific embodiment 9 in that it is used to prepare the positive electrode of an aqueous zinc ion battery, and is specifically carried out according to the following steps:
[0067] It is used to prepare the positive electrode of aqueous zinc ion battery, and is specifically carried out according to the following steps:
[0068] Tetrabutylammonium-coated MnV 13 , conductive agent, binder and N-methylpyrrolidone are mixed to obtain a homogenous slurry, and the coating amount is 0.7 mg / cm 2~1.0mg / cm 2 , coating the slurry on a current collector, and finally drying to obtain an aqueous zinc ion battery positive electrode;
[0069] The tetrabutylammonium-coated MnV 13 The mass ratio of the tetrabutylammonium-coated MnV 13 The mass ratio of the tetrabutylammonium-coated MnV 13 The mass of and the volume of N-methylpyrrolidone are 1g:(5-10)mL; the conductive agent is multi-walled carbon nanotubes; the adhesive is polyvinylidene fluoride. The rest is the same as the ninth embodiment.
[0070] The following examples are used to verify the beneficial effects of the present invention:
[0071] Embodiment 1:
[0072] A MnV based on tetrabutylammonium coating 13 The method for preparing the positive electrode material of the cluster water system zinc ion battery is carried out according to the following steps:
[0073] 1. 2.178g MnV 13 Dissolve in 50 mL of deionized water to obtain MnV 13 Solution;
[0074] The MnV 13 The structural formula is (NH4)7MnV 13 O 38 ;
[0075] 2. Dissolve 2.918 g of tetrabutylammonium chloride (TBA-Cl) in 150 mL of deionized water to obtain a tetrabutylammonium chloride solution;
[0076] 3. At a speed of 500 rpm, add 50 mL of MnV at a rate of 1 mL / min. 13 The solution was slowly added into 150 mL of tetrabutylammonium chloride solution and stirred for 1 h, and then the mixed solution was concentrated, centrifuged, washed and dried to obtain a dry powder;
[0077] 4. In an argon atmosphere, the dried powder was heated to 200°C at a heating rate of 5°C / min, and then calcined for 5 hours in an argon atmosphere at 200°C to obtain tetrabutylammonium-coated MnV 13 , namely TBA-MnV 13 ;
[0078] The tetrabutylammonium-coated MnV 13 The chemical formula is (NH4)2(C 16H 36 N)5MnV 13 O 38 .
[0079] The concentrated mixed solution in step 3 is specifically concentrated by using a rotary evaporator at a temperature of 60° C. and a rotation speed of 100 rpm until the solvent is completely evaporated.
[0080] The centrifugal washing described in step 3 specifically uses deionized water, centrifuges at a rotation speed of 8000 rpm for 10 minutes, and repeats the centrifugal washing three times.
[0081] The drying described in step 3 is specifically performed under vacuum drying at a temperature of 60° C. for 12 hours.
[0082] Example 2: MnV based on tetrabutylammonium coating prepared in Example 1 13 The application of the cluster aqueous zinc ion battery positive electrode material is used to prepare the aqueous zinc ion battery positive electrode, which is specifically carried out according to the following steps:
[0083] Tetrabutylammonium-coated MnV 13 , conductive agent, binder and N-methylpyrrolidone are mixed to obtain a homogenous slurry, and the coating amount is 1.0 mg / cm 2 , coating the slurry on a current collector, and then drying it in a vacuum oven at 60° C. to obtain an aqueous zinc ion battery positive electrode (a disc with a diameter of 10 mm);
[0084] The tetrabutylammonium-coated MnV 13 The mass ratio of the tetrabutylammonium-coated MnV 13 The mass ratio of the tetrabutylammonium-coated MnV 13 The mass of and the volume of N-methylpyrrolidone are 1g:10mL; the conductive agent is multi-walled carbon nanotubes; and the adhesive is polyvinylidene fluoride.
[0085] Comparative experiment: The difference between this comparative experiment and Example 2 is that the MnV coated with tetrabutylammonium 13 Replaced by MnV 13 The rest is the same as that of the second embodiment.
[0086] Figure 1 The TBA-MnV prepared in Example 1 13 With MnV 13 X-ray diffraction image comparison chart; Through the diffraction image, compared with MnV 13 In comparison, the TBA-MnV prepared after coating 13 The crystallinity of the material is significantly reduced, which means that MnV 13The composite transforms into an amorphous state, and the small-angle XRD pattern shows a distinct peak at 7.36°, corresponding to an intercluster spacing of ∼1.2 nm, which is consistent with the size of MnV coated with TBA cations. 13 The cluster sizes were highly consistent, confirming that MnV 13 Evenly coated with TBA.
[0087] Figure 2 The TBA-MnV prepared in Example 1 13 , TBA and MnV 13 Infrared spectrum of TBA and MnV 13 Coexistence with TBA-MnV 13 In complex, both TBA and MnV 13 Comparison of characteristic peaks of infrared spectra of TBA-MnV 13 The significant peak position in the composite material did not shift, which indicates that the coating process involves physical interaction rather than chemical bonding, thus maintaining the MnV 13 and the independent characteristics of TBA.
[0088] Figure 3 The TBA-MnV prepared in Example 1 13 Transmission electron microscope image of Figure 4 The TBA-MnV prepared in Example 1 13 High-resolution transmission electron microscopy image of TBA-MnV 13 This is consistent with the results of XRD. In addition, it can be clearly seen that the randomly arranged MnV 13 Clusters, this disordered arrangement facilitates ion transport.
[0089] Figure 5 The TBA-MnV prepared in Example 1 13 The element distribution diagram of the energy dispersive X-ray spectrum; it can be seen from the figure that C, N, Mn, V and O are evenly distributed in the whole composite material, which proves that MnV 13 Successfully wrapped by TBA.
[0090] Figure 6 The TBA-MnV prepared in Example 1 13 Thermogravimetric analysis curve under oxygen atmosphere; the curve reveals that TBA-MnV 13 The two-step mass loss process, the first stage of significant mass loss (220℃~350℃) is attributed to NH4 + and TBA thermal decomposition, accounting for 44% of the total mass loss; while the second stage (350℃~600℃) corresponds to NH4 +The decomposition of TBA-MnV accounted for 3%. Thermogravimetric analysis and organic element analysis supported the 13 The chemical formula is (NH4)2(C 16 H 36 N)5MnV 13 O 38 .
[0091] Example 3: Assemble button cells using the positive electrode of the aqueous zinc ion battery prepared in Example 2 and the comparative experiment: Take a piece of zinc sheet, use sandpaper to polish the entire zinc sheet to remove the surface oxide layer, then wash it with ultrapure water, and then put it into a constant temperature blast drying oven at 60°C to dry. The dried zinc sheet is cut into discs with a diameter of 10 mm on a slicer to serve as the negative electrode. Glass fiber is used as a battery separator, 3M Zn(CF3SO3)2 is used as an electrolyte, and CR2032 button cells are assembled in the air in the order of negative electrode shell, shrapnel, gasket, negative electrode sheet, separator, electrolyte, positive electrode sheet, and positive electrode shell, and then packaged with a battery packaging machine.
[0092] Figure 7 For Example 3, TBA-MnV 13 and MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell was tested at a voltage of 0.2 V to 1.8 V and a scan rate of 0.5 mV s -1 Cyclic voltammetry curve under the condition of TBA-MnV 13 The positive electrode exhibits two distinct pairs of redox peaks, at ~1.16 / 0.85 V and 0.88 / 0.48 V (compared to Zn / Zn 2+ ), and the peaks overlap well in the subsequent cycles, which means its excellent redox reversibility and stability; in contrast, MnV 13 The redox peaks of the positive electrode have a slight shift: 1.22 / 0.75V, 0.82 / 0.37V (compared with Zn / Zn 2 + ), and similar stable peak currents, reflecting its intrinsic reversible redox behavior.
[0093] Figure 8 For Example 3, TBA-MnV 13 and MnV 13 The charge and discharge curves of the button cell assembled with the prepared aqueous zinc ion battery positive electrode; As can be seen from the figure, TBA-MnV 13 showed a significantly higher 399.6 mAh g -1 Compared with the specific capacity of MnV 13 Only 275mAh g -1 In addition, it can be found that TBA-MnV13 The working voltage of TBA-coated MnV 13 This improves both the energy storage capacity and the reaction kinetics.
[0094] Fig. 9 For Example 3, TBA-MnV 13 and MnV 13 The button cell assembled with the prepared aqueous zinc ion battery positive electrode was operated at a current density of 0.2A -1 ~9Ag -1 Rate performance test curve under 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 , 2A g -1 , 3Ag -1 , 5Ag -1 , 7Ag -1 and 9Ag -1 Next, TBA-MnV 13 The average discharge capacity reached 338.6 mAh g -1 , 320.4mAh g -1 , 305.9mAh g -1 , 289.6mAh g -1 , 274.5mAh g -1 , 237.5mAh g -1 , 197.5mAh g -1 and 163.8mAh g -1 ; When the current density returns to 0.2A after high rate cycling -1 When -1 , which proves the excellent rate performance and structural stability. In addition, the battery -1 After 600 cycles at a current density of 1.34 W, the specific capacity remained at 298.5 mAh g -1 , reflecting its extraordinary cycling stability. In comparison, MnV 13 The positive electrode consistently showed lower capacity in tests at all current densities, proving that TBA coating improves the electrochemical performance of the material.
[0095] Fig.10 For Example 3, TBA-MnV 13 and MnV 13 Electrochemical impedance spectroscopy test of the button cell assembled with the prepared aqueous zinc ion battery positive electrode; it can be found that after 120 cycles, TBA-MnV 13 The charge transfer resistance is significantly lower than that of MnV 13, confirming its superior ion transmission performance.
[0096] Fig.11 For Example 3, TBA-MnV 13 The CV curves of the button cells assembled with the prepared aqueous zinc-ion battery cathode were measured at different scan rates; Fig.12 for Fig.11 The b values of the four groups of redox peaks in Fig.11 , TBA-MnV 13 The b-values of peaks 1 to 4 are 0.9426, 0.9820, 0.8402, and 0.9428, respectively, indicating that the charge storage mechanism is mainly pseudocapacitive.
[0097] Fig.13 For Example 3, TBA-MnV 13 The diffusion / capacitance contribution ratio calculated after measuring the CV curves of the prepared aqueous zinc-ion battery cathode assembled button cells at different scan rates;
[0098] Fig.14 For Example 3, MnV 13 The CV curves of the button cells assembled with the prepared aqueous zinc-ion battery cathode were measured at different scan rates; Fig.15 for Fig.14 The b values of the four groups of redox peaks in Fig.14 , MnV 13 The b values of the positive electrode are lower, 0.8302, 0.6089, 0.7921, and 0.6625, respectively, indicating that it relies more on the diffusion-controlled process.
[0099] Fig.16 For Example 3, MnV 13 The diffusion / capacitance contribution ratio of the coin cell assembled with the prepared aqueous zinc ion battery cathode was calculated after measuring the CV curve at different scan rates; Fig.13 Combined with the comparison, it can be found that TBA-MnV 13 The battery with MnV as the positive electrode active material has a charge storage mechanism mainly based on pseudocapacitance, while the control group has MnV 13 The charge storage mechanism of the battery with positive active material is more dependent on the diffusion-controlled process. -1 When TBA-MnV 13 The cathode achieves a capacitance contribution of up to 95%, highlighting its fast charge transfer kinetics and efficient Zn 2+ accessibility, and this high capacitance ratio gradually increases with the increase of scan rate. These results confirm that the TBA-coated MnV 13 The rapid Zn 2+Ion storage.
[0100] Fig.17 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the initial stage TBA-MnV 13 V 2p X-ray photoelectron spectrum; Fig.18 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the discharge stage TBA-MnV 13 V 2p X-ray photoelectron spectrum; Fig.19 For Example 3, TBA-MnV 13 The button cell assembled with the prepared aqueous zinc ion battery cathode during the charging stage TBA-MnV 13 V 2p X-ray photoelectron spectrum; combined with Fig.17 , 18 It can be found that at the beginning, TBA-MnV 13 The positive electrode mainly contains V 5 + , as the battery discharges to 0.2V, V 5+ Consumption and V 3+ and V 4+ The appearance of the Zn ions indicates that a multi-electron reduction process occurs with the insertion of Zn ions. As the charging begins, the reduced vanadium atoms are oxidized back to a higher valence state, and the Zn ions are de-intercalated during the process, proving the reversible valence cycle and the TBA-MnV 13 Stable redox activity of electrode materials.
[0101] Fig. 20 For Example 3, MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the initial stage MnV 13 V 2p X-ray photoelectron spectrum; Fig.21 For the use of MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the discharge stage MnV 13 V 2p X-ray photoelectron spectrum; Fig. 22 For the use of MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the charging stage MnV 13 V 2p X-ray photoelectron spectrum; combined with Fig. 20 , 21 , it can be seen that the MnV tested under the same conditions 13 The positive electrode exhibits limited valence state adjustment capability. After discharge to 0.2 V, MnV 13 The main one is V 5+ and V4+ , almost no low-valent vanadium (V) species are formed. The comparison highlights the crucial role of TBA coating in further redox reactions and multi-electron conversion, making TBA-MnV 13 Compared with its MnV 13 The counterparts have superior redox activity and energy storage capacity.
[0102] Fig.23 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell during the second charge and discharge (activation) period 51 V NMR spectrum; Fig.24 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the twelfth cycle (after activation) 51 V NMR spectrum; combined Fig.23 No significant changes in chemical shifts or peak shapes were found. This invariance suggests that the basic VO coordination framework remains intact despite repeated redox cycles. 2+ The introduction of TBA-MnV 13 The structure maintains its chemical integrity and coordination environment during long-term operation.
[0103] Fig.25 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell in the discharge stage TBA-MnV 13 Zn 2p X-ray photoelectron spectrum of the cathode; indicating that zinc ions are embedded in the cathode material during the discharge phase.
[0104] Fig.26 For Example 3, TBA-MnV 13 The button cell assembled with the prepared aqueous zinc ion battery cathode during the charging stage TBA-MnV 13 Zn 2p X-ray photoelectron spectrum of the positive electrode; indicating that zinc ions are deintercalated from the positive electrode material during the charging stage.
[0105] Fig. 27 For Example 3, MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell at 1.0Ag -1 Cyclic performance diagram of 2700 cycles at a current density of , 1 is the Coulomb efficiency curve, 2 is the discharge specific capacity curve; Fig.28 For Example 3, TBA-MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell at 1.0Ag-1 The cycle performance diagram of 2700 cycles at a current density of , 1 is the Coulomb efficiency curve, 2 is the discharge specific capacity curve; and Fig. 27 Combined with the comparison, it can be found that TBA-MnV 13 The positive electrode initially showed 300.4 mAh g -1 The high capacity can still reach 258.7 mAh g after 2700 cycles. -1 , while the Coulombic efficiency is close to 100%. On the contrary, MnV 13 The positive electrode showed a strong capacity loss, with the specific capacity decreasing from 173.5 mAh g at the initial stage to 173.5 mAh g after 2700 cycles. -1 Reduced to 19.7 mAh g -1 ,The above can explain that the improvement of cycle performance and capacity is mainly attributed to the coating of TBA, which improves the structural integrity and reduces the structural degradation.
[0106] Fig.29 For Example 3, TBA-MnV 13 and MnV 13 The prepared aqueous zinc ion battery positive electrode assembled button cell at 0.2Ag -1 300 cycles test diagram at a current density of 0.2Ag -1 At low current density, TBA-MnV 13 The specific capacity after 300 cycles is 289.9 mAh g -1 , the capacity retention rate reaches 80%. In comparison, MnV 13 The specific capacity of the positive electrode after 300 cycles is only 93.1 mAh g -1 (only 47% of the initial capacity). Such improvement in cycle performance and capacity is mainly attributed to the TBA coating, which improves the structural integrity of the positive electrode material and reduces structural degradation.
[0107] Fig.30 For Example 3, TBA-MnV 13 Comparison of the energy density and power density of the button cell assembled with the prepared aqueous zinc ion battery cathode and the reported vanadium-based cathode materials; TBA-MnV 13 The energy density and power density of the button battery reached 237Wh kg -1 and 4.6kW kg -1 As can be seen from the figure, this exceeds many reported vanadium-based cathode materials. It can be considered that TBA-MnV 13 It is a very promising cathode material for advanced aqueous zinc-ion batteries;
[0108] Fig.30References for VO2(B) material data: Ding, J.; Du, Z.; Gu, L.; Li, B.; Wang, L.; Wang, S.; Gong, Y.; Yang, S., Ultrafast Zn 2+ Intercalation and Deintercalation in VanadiumDioxide.Advanced Materials 2018,30(26)1800762.
[0109] Fig.30 Medium Mg x V2O5×nH2O material data reference: Genovese, M.; Lian, K., Polyoxometalatemodified inorganic-organic nanocomposite materials for energy storage applications: A review. Current Opinion in SolidState andMaterials Science2015,19(2),126-137.
[0110] Fig.30 ZhongNa 0.33 V2O5 material data reference: He, P.; Zhang, G.; Liao, X.; Yan, M.; Xu,
[0111] Fig.30 Na2V6O 16 ×1.63H2O material data reference: Hu, P.; Zhu, T.; Wang, X.; Wei, X.; Yan, M.; Li, J.; Luo, W.; Battery.Nano Letters2018,18(3),1758-1763.
[0112] Fig.30 Medium Zn 0.25 V2O5 substance data reference: Kundu, D.; Adams, BD; Duffort, V.; Vajargah, SH; Nazar, LF.
[0113] Fig.30 Reference for the material data of NaV3O8×1.5H2O: Wan, F.; Zhang, L.; Dai, X.; Wang, X.; Niu, Z.; Chen, J., Aqueous rechargeable zinc / sodium vanadate batteries with enhanced performance from simultaneous insertion of dual carriers. Nature Communications 2018, 9(1), 1656.
[0114] Fig.30 Reference for VOPO4 material data: Wan, F.; Zhang, Y.; Zhang, L.; Liu, D.; Wang, C.; Song, L.; Niu, Z.; Chen, J., Reversible Oxygen Redox Chemistry in Aqueous Zinc-Ion Batteries. Angewandte Chemie International Edition 2019, 58(21), 7062-7067.
[0115] Fig.30 Reference for bulk V2O5 material data: Zhou, J.; Shan, L.; Wu, Z.; Guo, X.; Fang, G.; Liang, S., Investigation of V2O5 as a low-cost rechargeable aqueous zinc ionbattery cathode. Chemical Communications 2018, 54(35), 4457-4460.
[0116] Fig.31 For Example 3, TBA-MnV 13 The self-discharge test of the button cell assembled with the prepared aqueous zinc ion battery positive electrode after standing for 48 hours; Fig.32 For Example 3, MnV 13 The self-discharge test diagram of the button battery assembled with the prepared aqueous zinc ion battery positive electrode after standing for 48 hours; Fig.31 Compared with the comparative example, after standing for 48 hours, TBA-MnV 13 The cathode retained 88.75% of its initial capacity, outperforming the MnV which retained 85.07% capacity under the same conditions. 13 In addition, during the static self-discharge process, based on TBA-MnV 13 The battery is stable at 1.15V, and its MnV 13 The counterpart dropped to 1.09 V. These results indicate that TBA coating endows the material with significant structural and electrochemical stability.
Claims
1. A MnV based on tetrabutylammonium coating 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that It is carried out in the following steps:
1. MnV 13 Dissolve in deionized water to obtain MnV 13 Solution; 2. dissolving tetrabutylammonium chloride in deionized water to obtain a tetrabutylammonium chloride solution; 3. Under stirring conditions, MnV 13 The solution is slowly added to the tetrabutylammonium chloride solution and stirred, and then the mixed solution is concentrated, centrifuged, washed and dried to obtain a dry powder; 4. The dried powder was calcined under argon atmosphere to obtain tetrabutylammonium-coated MnV 13 , that is, to complete the MnV based on tetrabutylammonium coating 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery; The tetrabutylammonium-coated MnV 13 The chemical formula is (NH4)2(C 16 H 36 N)5MnV 13 O 38 .
2. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that MnV as described in step 1 13 The mass ratio of the deionized water to the volume ratio is 1g:(20~30)mL.
3. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that The mass ratio of tetrabutylammonium chloride described in step 2 to the volume ratio of deionized water is 1 g: (50-60) mL.
4. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that MnV as described in step 3 13 The volume ratio of the solution to the tetrabutylammonium chloride solution is 1:(3-4).
5. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that In step 3, MnV is added at a speed of 1 mL / min to 2 mL / min at a rotation speed of 500 rpm to 800 rpm. 13 The solution was slowly added into tetrabutylammonium chloride solution and stirred for 1 h to 2 h.
6. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that The concentrated mixed solution described in step three is specifically concentrated by using a rotary evaporator at a temperature of 50°C to 60°C and a rotation speed of 100rpm to 120rpm until the solvent is completely evaporated; the centrifugal washing described in step three is specifically using deionized water, at a rotation speed of 8000rpm to 10000rpm, centrifugal washing for 5min to 10min, and repeating the centrifugal washing for ≥3 times.
7. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that The drying described in step 3 is specifically performed at a temperature of 50° C. to 60° C. and vacuum drying for 12 h to 16 h.
8. A tetrabutylammonium-coated MnV according to claim 1 13 A method for preparing a positive electrode material for a cluster aqueous zinc ion battery, characterized in that In step 4, the temperature is raised to 200°C to 250°C at a heating rate of 3°C / min to 5°C / min under an argon atmosphere, and then calcined for 5h to 6h under the conditions of an argon atmosphere and a temperature of 200°C to 250°C.
9. A tetrabutylammonium-coated MnV as claimed in claim 1 13 Application of cluster aqueous zinc ion battery positive electrode material, characterized in that It is used to prepare the positive electrode of aqueous zinc ion batteries.
10. A tetrabutylammonium-coated MnV according to claim 9 13 Application of cluster aqueous zinc ion battery positive electrode material, characterized in that It is used to prepare the positive electrode of aqueous zinc ion battery, and is specifically carried out according to the following steps: Tetrabutylammonium-coated MnV 13 , conductive agent, binder and N-methylpyrrolidone are mixed to obtain a homogenous slurry, and the coating amount is 0.7 mg / cm 2 ~1.0mg / cm 2 , coating the slurry on a current collector, and finally drying to obtain an aqueous zinc ion battery positive electrode; The tetrabutylammonium-coated MnV 13 The mass ratio of the tetrabutylammonium-coated MnV 13 The mass ratio of the tetrabutylammonium-coated MnV 13 The mass of and the volume of N-methylpyrrolidone are 1g:(5-10)mL; the conductive agent is multi-walled carbon nanotubes; and the adhesive is polyvinylidene fluoride.
Citation Information
Patent Citations
Polyoxometalate cluster organic amine salt and preparation method thereof
CN104119232A
Secondary battery, battery module, battery pack, and electric device
CN116998040A
Application of multi-vanadium oxygen cluster material in preparation of aqueous zinc storage positive electrode
CN117038949A
Negative electrode for metal air battery and metal air battery using the same
JP2024094991A
Vanadium oxide-based anode material for zinc-ion battery, manufacturing method therefor, and zinc-ion battery comprising same
WO2023038244A1